2003
DOI: 10.4000/chs.545
|View full text |Cite
|
Sign up to set email alerts
|

Running away and returning home: the fate of English convicts in the American colonies

Abstract: Transportation of criminals to America was one of the distinctive features of English penal policy in the eighteenth century. While other countries experimented with the practice, only Britain undertook large-scale convict transportation after 1700, a policy which Pieter Spierenburg regards as a departure from the European norm 2. Eighteenth century Continental critics certainly regarded it as a curiosity: «Banishment seems to be an assault on international rights», Denis Diderot wrote in reaction to equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…(2008: 286)This profile of transported offenders remained constant even after the 1718 Act. In their study of 4,500 offenders transported from northern England between 1718 and 1776, Rushton and Morgan (: 63) found that their subjects had been “convicted for mostly petty offences. Indeed, only about a third of those transported from assize courts had been condemned to death and reprieved on condition of transportation.” These findings suggest that many who were transported would have received some punishment less severe than capital punishment.…”
Section: The Relationship Between Transportation and Capital Punishmentmentioning
confidence: 99%
“…(2008: 286)This profile of transported offenders remained constant even after the 1718 Act. In their study of 4,500 offenders transported from northern England between 1718 and 1776, Rushton and Morgan (: 63) found that their subjects had been “convicted for mostly petty offences. Indeed, only about a third of those transported from assize courts had been condemned to death and reprieved on condition of transportation.” These findings suggest that many who were transported would have received some punishment less severe than capital punishment.…”
Section: The Relationship Between Transportation and Capital Punishmentmentioning
confidence: 99%